Contrastar el sistema del seguro social en Colombia antes de la ley 100 de 1993 y la actual propuesta reforma a la salud en el 2023 (2024)
Law 100 of 1993 introduced important changes in the health system, including the creation of the General Social Security Health System (SGSSS), which sought to guarantee universal access to health services and improve the quality of medical care. However, the health system in Colombia continues to face significant challenges. In recent decades, there have been additional changes in health and social security legislation in the country, which has led to the question of what are the similarities and differences between the social insurance system prior to Law 100 and the current one. health system in Colombia, even creating a new proposal to reform the system. Therefore, the objective of this research focuses on contrasting the social security system in Colombia before Law 100 of 1993 and the current proposed health reform in 2023 through a comparative descriptive approach using a rigorous review of the literature. The discussion of the results reveals that Law 100 of 1993 allowed the unification of regulations and established fundamental pillars such as universality, efficiency, solidarity and comprehensiveness, thus strengthening well-being and equity in society. This allowed us to conclude that a reform that rather guarantees equitable and efficient access to health, strengthening Primary Health Care (PHC), increasing investment in primary care centers and the network of professionals, which would improve access to services preventive, diagnostic and basic treatments